Gait Planning of Lower Extremity Exoskeleton Climbing Stair based on Online ZMP Correction - Zhenzhong Yu; Jintao Yao (Jixie chuandong)
In order to improve the stability of the lower extremity exoskeleton robot climbing the stair， the reasonable gait planning and error correction are two important aspects. To this end， an online correction method of zero moment point (ZMP) during the stair step is proposed. Firstly， the movement model of the lower limbs climbing the stairs is established， the kinematics analysis is performed， and the lower limb joint trajectory planning is performed by using the 5 times B-spline curves. Secondly， the online ZMP correction is used to adjust for large errors between the actual and planned ZMP trajectories caused by unstable disturbances in the wear process. Finally， through simulation and actual experiments， this online correction can significantly reduce the ZMP error of the robot， improve the stability margin of the robot ZMP， and ensure the overall stability of the lower limb robot system.